Perceptually guided Computer-Generated Holography - Aksit, Kaan; Kavakl, Koray; Walton, David; Steed, Anthony; Urey, Hakan; Dos Anjos, Rafael Kuffner; Friston, Sebastian; Weyrich, Tim; Ritschel, Tobias (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
Computer-Generated Holography (CGH) promises to deliver genuine, high-quality visuals at any depth. We argue that combining CGH and perceptually guided graphics can soon lead to practical holographic display systems that deliver perceptually realistic images. We propose a new CGH method called metameric varifocal holograms. Our CGH method generates images only at a user’s focus plane while displayed images are statistically correct and indistinguishable from actual targets across peripheral vision (metamers). Thus, a user observing our holograms is set to perceive a high quality visual at their gaze location. At the same time, the integrity of the image follows a statistically correct trend in the remaining peripheral parts. We demonstrate our differentiable CGH optimization pipeline on modern GPUs, and we support our findings with a display prototype. Our method will pave the way towards realistic visuals free from classical CGH problems, such as speckle noise or poor visual quality.
CRIS-Team Scopus Importer:2022-07-26
Keywords: Computer-Generated Holography; Differentiable Optimization; Foveated Rendering; Gaze-Contingent; Metamerization; Perceptual Graphics; Varifocal